J.K. Lasser's small business taxes 2011 : Your complete guide to a better bottom line - Weltman, Barbara , 1950-; Lasser, J. K. [ (Jacob Kay)] , 1896-1954 (John Wiley & Sons, 2011)
The tax facts and strategies that every small business owner needs to know Written in a straightforward and accessible style, this reliable resource offers a complete overview of small business tax planning and provides you with the information needed to make tax-smart decisions throughout the year